Social psychology of violence against minority groups: the legitimising role of justice perceptions - Mateus, Karla Santos (2020)
Black people, women and homosexuals are groups of individuals who severely suffer with intentional violence in the world and are commonly secondarily victimized by both citizens and institutions. The persistence of this type of violence and the social support it encounters is based on a legitimation process. This process often involves different perceptions and a desire for justice. Based on recent literature addressing the social psychology around legitimation processes of social inequalities, this thesis proposes the hypothesis that perceptions of justice, such as secondary victimization, work as a justification for discrimination against social minorities in situations of violence. To test the hypothesis proposed here, we developed a research program in which we carried out three experimental studies and a correlational one, which we present throughout two different articles. In the first piece, we preliminarily tested our hypothesis in two experimental studies on violence against minority groups (black people vs. women vs. homosexuals). In Study 1 (N = 104), the results revealed that participants blamed more women for their own victimization, in addition to holding the aggressor less accountable when the victim was black, and described homophobic violence as a common social issue similar to the general violence that occurs in society. Study 2 (N = 217) took it a step further and demonstrated that these effects occur mainly when participants are asked to respond according to what society thinks. In the second article, we conducted two new studies with the aim of testing whether the secondary victimization of an aggression victim is related to prejudice and the belief in a just world (BJW). In Study 1 (N = 102), we manipulated the hints about the sexual orientation of a man who was a victim of violence and we found that the most prejudiced participants minimized the victim's suffering and blamed them more once they realized this victim was a homosexual. Study 2 (N = 205) replicated the role of prejudice in this secondary victimization and revealed that, in participants with a high BJW, prejudice motivates the minimization of the victim's suffering when they are perceived as a homosexual. We discussed the set of results in the context of the Justified Discrimination Model, highlighting the role of prejudice, BJW and secondary victimization in the process of legitimizing violence against minority groups.